Communication from the executive of the Commonwealth, transmitting a list of vessels employed by the state of Virginia as reported by Captain S. Barron - Barron, Samuel, 1809-1888 (LLMC-digital (Series), 1861)
Governor John Letcher's transmittal letter of Captain Barron's report dated June 24 1863 (that is 1861) regarding vessels employed by the state of Virginia.